Effect of vitamin d therapy on synovial tissue volume and bone marrow lesions in symptomatic knee osteoarthritis - Perry, TA; O'Neill, TW; Parkes, MJ; Felson, DT; Hodgson, R; Arden, NK (Elsevier, 2018)
Vitamin D has biological effects on multiple knee joint structures and data from observational studies suggest vitamin D deficiency may be linked with pain and progression of knee OA. In the UK VIDEO study, a multicentre 3-year randomised placebo controlled trial of vitamin D therapy (800 IU/day) in patients with symptomatic knee OA, there was no evidence of an effect of vitamin D therapy on either pain or structural progression of disease as assessed using x-rays. We hypothesised, however, that there may be an effect of treatment on the occurrence of synovial tissue volume (STV) and bone marrow lesions (BMLs), as assessed by magnetic resonance imaging (MRI).